A Review of Applications of Rotating and Vibrating Membranes Systems: Advantages and Drawbacks - Jaffrin, Michel Y.; Ding, Luhui (Journal of Membrane and Separation Technology, 2015)
Dynamic filtration (DF) consists in creating a high membrane shear rate by disks rotating near a fixed membrane or by rotating or vibrating membranes. The shear rate can exceed 3 105s-1 in some modules and significantly increases permeate flux and membrane selectivity as compared to cross flow (CF) devices. This paper describes several DF industrial modules and gives equations for calculating shear rates at rotating and vibrating membranes. It reviews 23 recent articles from 2008 to 2014, dealing with diverse applications: separation of microalgae from sea water by UF, clarification of rough beer, concentration of CaCO3 suspensions, treatment of dairy effluents and shipboard wastewaters, inulin extraction from chicory juice, treatment of oil field water, and separation of bovine albumin from yeast. In several applications, the maximum permeate flux at initial concentration ranged from 270 to 760 Lh-1m-2. Modules with ceramic membranes rotating around several shafts inside a housing seem to be preferable to the concept of multi-compartments modules with metal disks rotating between fixed membranes. Since the cost of DF modules is higher than that of spiral wound ones, it is better to apply DF to ”end of pipe treatment” after an initial concentration by CF.